The Size Effect on the Optical-Electrical Properties of Cu2s/Cds Thin Film Towards the Performance on Ag/P-Cu2s/N-Cds/Ato Heterojunction Diode - Singh, D (Elsevier Ltd, 2023)
Here we report, room temperature deposition of Cu2S/CdS thin film on antimony doped tin oxide(ATO) substrate through spray pyrolysis and dip coating technique. The effect of size on the deposited Cu2S/CdS thin films and its heterojunction parameters are extensively investigated. The sizes of the thin film are estimated through field-emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) images. The optical properties of the Cu2S/CdS thin film are studied using UV–Vis–NIR spectrometer. It is found that increase in the size, the transmittance decreases, consequently the band-gap energy decreases from 2.92eV to 2.86eV. The refractive index and the dielectric constant are calculated from the optical measurements. In addition, the dispersion of the refractive index is discussed in terms of the Wemple-DiDomenico single-oscillator model. The oscillator parameters such as optical dispersion energies, dielectric constant, the average value of oscillator strength, wavelength of single oscillator, plasma frequency and lattice energy are evaluated. To examine the size-dependent electrical parameters of Cu2S/CdS thin film, high-quality vacuum evaporated silver (Ag) is used as front contact. The current-voltage (I–V) curves of the Ag/p-Cu2S/n-CdS/ATO/glass heterojunction device are measured under dark mode at standard testing conditions (STC). The dark measurements of the fabricated device are investigated through the conventional I–V method, Norde method, and Cheung method. It is observed that the potential height of the heterojunction device decreases from 0.89 to 0.76 with an increment of the size of Cu2S/CdS thin films. It is observed that the size strongly influenced the diode parameters viz. ideality factor, saturation current, barrier height, series, and shunt resistance performance. © 2023 Elsevier B.V.